Effect Of Non-Uniformity Of The Multiconductor Line Constructional Parameters On The Frequency Characteristics Of The Meander Microstrip Delay Line - Audrius Krukonis; Šarūnas Mikučionis (Mokslas: Lietuvos Ateitis, 2014)
Inhomogeneities of the electromagnetic field are observed at the edges of the electrodynamic delay systems which are designed based on the concept of infinite periodic multiconductor line. The influence of non-uniformity of characteristic impedance and effective permittivity of the multiconductor microstrip line on the frequency responses and characteristics of meander microstrip delay lines is studied in this paper. It is shown that aligning characteristic impedance and effective permittivity of the multiconductor line the bandwidth of the delay line can be significantly extended.